Improving soil health is central to the climate-smart agriculture approach - Trautman, Sabrina (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Poster 1: This poster describes the links between improving soil health and climate-smart agriculture (CSA). It illustrates the three pillars of CSA and gives examples of practices under each which either involve improved soil management activities or contribute to enhanced soil health.